1971
DOI: 10.1042/bj1230559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a neutral protease from lysosomes of rabbit polymorphonuclear leucocytes

Abstract: 1. The subcellular distribution has been investigated of a protease from rabbit polymorphonuclear leucocytes, obtained from peritoneal exudates. The enzyme, optimally active between pH7.0 and 7.5, hydrolyses histone but not haemoglobin, sediments almost exclusively with a granule fraction rich in other lysosomal enzymes, and is latent until the granules are disrupted by various means. 2. Enzymic analysis of specific and azurophilic granules separated by zonal centrifugation showed that neutral protease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…By contrast, the proteolytic activity of rabbit polymorphonuclear leucocytes is mainly at acid pH values (Davies et al, 1971;Ignarro et al, 1973)andtheproteoglycan-degradingactivityhasbeen found to show a similar characteristic (Weissmann & Spilberg, 1968;Oronsky et al, 1973). It was therefore surprising that we found greater activity at pH7.6 than at pH4.5 in the bead assay for proteoglycan-degrading activity.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the proteolytic activity of rabbit polymorphonuclear leucocytes is mainly at acid pH values (Davies et al, 1971;Ignarro et al, 1973)andtheproteoglycan-degradingactivityhasbeen found to show a similar characteristic (Weissmann & Spilberg, 1968;Oronsky et al, 1973). It was therefore surprising that we found greater activity at pH7.6 than at pH4.5 in the bead assay for proteoglycan-degrading activity.…”
Section: Discussionmentioning
confidence: 99%
“…In Davies' [7] opinion, who obtained leucocytes by glycogen induction, the inhibitor uptake from plasma is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Davies and coworkers [7] reported in their study of neutral proteinases of polymorphonuclear cells that cytoplasmic -postgranular supernatant fraction caused the strongest inhibition of neutral proteinases. Because the polymorphonuclear cells were obtained from inflammatory exudates, they proposed a possibility of inhibitor uptake from plasma.…”
mentioning
confidence: 99%
“…elastase-like enzymes, in distinction to human leucocytes (Ohlsson & Olsson, 1973Schmidt & Havemann, 1974), Hence postulated species-dependent differences in the enzymic pattern of leucocyte neutral proteinases (Davies et al, 1971;Dewald et al, 1975) seem to be confirmed.…”
Section: Discussionmentioning
confidence: 97%